Examining a congruency-typology model of leadership for learning using two-level latent class analysis with TALIS 2018 - Bowers, Alex J.. (OECD Publishing, 2020)
Are teachers and principals aligned in their perceptions of the core components of the theory of Leadership for Learning across countries, or are there subgroups of schools in which there is misalignment? The purpose of this study is to examine the extent to which a congruency-typology model of leadership for learning is distributed across countries/economies using the TALIS 2018 dataset through examining the interaction of significantly different subgroups of teacher and principal responders through using multilevel latent class analysis (LCA) with a cross-level interaction. I analyse data from lower secondary schools of n=152 635 teachers in 9 079 schools and their principals across 47 countries/economies. Currently in the research literature on school leadership, leadership for learning has emerged as a framework to bring together managerial, transformational, distributed, and instructional leadership. Yet little is known about leadership for learning across national contexts. This study 1) maps the TALIS 2018 survey items to the current literature and surveys for leadership for learning, 2) then details the methods and analysis framework to examine if there are multiple significantly different types of teachers, principals, and schools from a leadership for learning theory framework. The final model 3) identifies a three-group teacher typology and a three-group principal typology, linking these types to school context, covariates, as well as teacher and principal training and experience. Results relate directly to the intersection of research, policy, and practice for training and capacity of school leaders across 47 countries/economies globally
Keywords: Education